Writing the commons to support citizen struggles in South East Europe: Interview with Tomislav Tomašević and the Institute for Political Ecology of Zagreb - Porche, Valentine; Jeanmougin, Cécile (Sens public)

(untitled) (Département des littératures de langue française, 2019)
Tomislav Tomašević and the Institute for Political Ecology (IPE) of Zagreb undertook the first inventory of Commons initiatives on the territory of the former Yugoslavia, coupled with the formulation of a narrative arising from these different experiences. This work was published in 2018 as a book entitled Commons in South East Europe (SEE). The strengths of the book are to be found in the resolutely critical approach to the “classical” definitions of the commons inherited from, among others, Elinor Ostrom, and in the historical perspective providing valuable knowledge about the experiments of “social property” and other practices of the commons in socialist Yugoslavia. Tomislav Tomašević, representative of the municipalist citizen movement named “Zagreb is Ours !”, mobilizes the narrative produced by his research as a tool to legitimate the political struggle led by citizens in favor of the commons, ecological conservation and economic democracy. In this interview, Tomašević explains the dynamics between the “formulation” of the commons experiences in the region and the revival of political struggles supporting the re-appropriation of spaces, services and public policies.